An analytical model for merged GaN heterojunction barrier Schottky diodes with inserting p-Si technology. (February 2021) - Wang, Wei; Li, Xiao-Xi; Xiao, Zhi-Qiang; Huang, Wei; Ji, Zhi-Gang; Chiang, Te-Kuang; Zhang, David Wei; Lu, Hong-Liang
Abstract: A novel combined GaN/Si device based on compatible CMOS semiconductor, merged heterojunction barrier Schottky (MHBS) diode is put forward and its generalized analytical heterojunction model is further built and validated. The fully two-dimension (2D) analytical model is developed based on new structure of the MHBS diode, which replaces the conventional junction-based region with inserting p-type Si technology. It provides a novel expression of potential and electric field distribution. The results of the fully 2D analytical model are validated in comparison with the numerical simulations for various device parameters, such as junction spacing widths and junction depths as well as reverse biases. Based on the derived reverse surface electric filed, the reverse I-V characteristics are also calculated by using the reverse conduction mechanism. The conduction band energy diagram is applied to analyze the reverse characteristic. Furthermore, the concept of shielding effect factor ( ξ ) and electric field coefficient of α are proposed for trading off the shielding tolerance of reverse biased MHBS diode compared with Schottky diode. As a result, this device modeling would be easily used for device design and provides a comprehensive physical understanding for GaN based MHBS diode as well. Highlights: Proposing novel GaN/Si device, merged heterojunction barrier Schottky diode. Replacing junction-based region with inserting p-Si by feasible, also develop the compatible GaN/CMOS process technology to solve the bottleneck of conventional GaN MPS or JBS device employing GaN with magnesium impurity as p-type. Deriving and validating fully 2D analytical model with simulator. Proposing new concepts of shielding effect factor. Device modeling is useful for device design and physical understanding.